Pendugaan Biomassa Eucalyptus urograndis IND 47 di Estate A, Sektor Aek Nauli, PT Toba Pulp Lestari Tbk - Rudianto Gurning; Siti Latifah; Kansih Sri Hartini (Peronema Forestry Science Journal, 2014)
The hybrid Eucalyptus urograndis IND 47 is a hybrid between Eucalyptus urophylla ST Blake and Eucalyptus grandis ex Maid W.Hill developed in operational scale in PT Toba Pulp Lestari Tbk (TPL). Therefore, a research had been  conducted on E. urograndis IND 47 in Estate A, sector of Aek Nauli, PT TPLTbk. The aim of this research was to predict biomass of E. urograndis IND 47. The results showed that the biomass of E.urograndis IND 47 in Estate A was 8,431.25 tons for total area of 367.38 ha compartment with an average biomass was 22.95 tons /ha with ages of 1-3.3 years. Biomass differences caused by differences in ages of trees, number of trees in each compartment and environmental factors.Keywords: biomass, Eucalyptus urograndis IND 47, PT Toba Pulp Lestari Tbk